Between “Pure Theory of Law” and Legal History: Kelsen and the Alleged “Antithesis” of Public and Private Law (Antologia di Diritto Pubblico, 2024)
This paper proposes a historical-juridical reading of Kelsen’s essay on public and private law, in a double sense: as a reconstruction of the meaning that this distinction had in the first decades of the 20th century, and as an analysis of its disputed origins, not only in the context of Roman law but also in the Greek legal culture.
Keywords: Hans Kelsen; public and private law; pure theory of law; ancient laws and western legal tradition; theory and history of law